TINGKAT PENGETAHUAN DAN SIKAP TENTANG CUCI TANGAN PAKAI SABUN (CTPS) PADA SISWA SDN BATUAH I DAN BATUAH III PAGATAN - Ratna Setyaningrum; Achmad Rofi’i; Annisa Setyanti (Lambung Mangkurat, 2015)
Abstract One indicator of healthy and clean life behaviour is hand washing with soap. Habits of Indonesian community in hand washing with soap is still relatively low, the indication can be seen by the high prevalence of diarrheal disease. Hand washing with soap focus is school student as